Reduction of xerostomia in head and neck cancer patients. A critical review of the literature. Issue 1 (December 2016) - Hanley, O.; Leech, M.
Abstract: Background: Radical radiotherapy given with or without concurrent chemotherapy is the main treatment modality in non-surgical patients for the management of squamous cell carcinoma in the head and neck. Xerostomia, which results from reduced salivary production is a debilitating side-effect of radiation therapy to these patients. Xerostomia may greatly impact on quality of life for head and neck cancer patients for up to 24 months post-radiation therapy. Such effects include difficulties in fundamental daily activities such as speech, mastication and swallowing. It is believed that modulated techniques provide better sparing to surrounding salivary glands. The aim of this critical review of the literature is to investigate what advantage intensity modulated radiotherapy (IMRT) can provide over 3 dimensional conformal radiation therapy (3DCRT) in reducing xerostomia in this subset of patients. Search methodology: An extensive literature search was undertaken to compare the incidence of grade 2 or worse xerostomia in HNSCC patients treated with IMRT or 3DCRT (±chemotherapy). Results: Studies reported a lower incidence of grade 2 or worse xerostomia with IMRT over patients treated with 3DCRT. The highest incidence of xerostomia was reported at 6 months following the completion of radiotherapy treatment. The incidence of xerostomia in patients declined with time, in both patients treated with IMRT and those of the 3DCRT cohort. The incidence of xerostomia was greater in the acute setting than in the late. Conclusion: An IMRT technique can consistently reduce grade 2 or worse xerostomia in head and neck cancer patients over conformal techniques. This will not compromise dose homogeneity or dose coverage. IMRT should remain the standard of care for head and neck patients. Highlights: IMRT technique can consistently reduce grade 2 or worse xerostomia in head and neck cancer patients over 3DCRT. IMRT does not compromise the treatment's dose homogeneity or dose coverage. IMRT should remain the standard of care for head and neck patients as the incidence of xerostomia is consistently reduced.